Collecting germplasm in Lesotho - Padulosi, S.; Laghetti, G. (1990)
Reports the findings of a collecting mission in Lesotho carried out by the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria and the Germplasm Institute CNR, Bari, Italy in April 1988. The main objective was to collect genetic resources of cowpea and bambara groundnut, and gather information about wild species of the genus Vigna in the country. 46 accessions of local varieties of cowpea were collected, together with 26 Phaseolus vulgaris, 6 Triticum aestivum,24 Zea mays and 16 other accessions.